2019
DOI: 10.1111/dmcn.14361
|View full text |Cite
|
Sign up to set email alerts
|

Performance of Upper Limb module for Duchenne muscular dystrophy

Abstract: Aim To report the differences between Performance of Upper Limb (PUL) versions 1.2 and 2.0, compare the measurement ability of the two versions, and compare their longitudinal performance in Duchenne muscular dystrophy. Method Rasch analysis was performed on the dual data from three centres to confirm whether the two scales measure the same construct. Change scores in natural history for the different domains were compared for the two versions. Results Rasch analysis demonstrated that both versions measure the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
76
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 14 publications
(28 reference statements)
2
76
0
Order By: Relevance
“…Finally, the PUL module demonstrated to have inter-rater reliability, as demonstrated by ten independent assessors. The comparability and the possibility of using PUL 1.2 and 2.0 versions in longitudinal studies have been shown [37]. This study demonstrated the robustness and reliability of the PUL module and, as a consequence, this clinical scale can be suggested as a primary outcome measure in experimental clinical trials involving patients diagnosed with muscular dystrophy other than DMD, such as LGMD and BMD.…”
Section: Discussionmentioning
confidence: 63%
See 2 more Smart Citations
“…Finally, the PUL module demonstrated to have inter-rater reliability, as demonstrated by ten independent assessors. The comparability and the possibility of using PUL 1.2 and 2.0 versions in longitudinal studies have been shown [37]. This study demonstrated the robustness and reliability of the PUL module and, as a consequence, this clinical scale can be suggested as a primary outcome measure in experimental clinical trials involving patients diagnosed with muscular dystrophy other than DMD, such as LGMD and BMD.…”
Section: Discussionmentioning
confidence: 63%
“…PUL module has the advantage of providing evidence on the functional evolution over time of the disease from distal to proximal levels. After the beginning of this study, a novel version of the PUL module (PUL 2.0) has been validated and shared with the scientific community [13,36,37]. PUL 2.0 is constituted by 22 items, and some items of the previous version were deleted (i.e., items B, I, K, U, and V).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The current PUL scale is of version 1.3. This year in 2019, an updated version 2.0 has been established for patients with DMD [10] and the study con rmed that both PUL versions measure the same construct so the current study ndings can be generalized to the use of PUL version 2.0 in addition we understand that the update version could be better in detecting the serial changes when checked in 12 months or 24 months interval.…”
Section: Limitations and Future Research Directionsmentioning
confidence: 57%
“…The development of Performance of the Upper Limb module (PUL) for Duchenne muscular dystrophy [8,9] was rst established in 2013. There is also an updated version of PUL 2.0 [10].…”
Section: Introductionmentioning
confidence: 99%